Neonatal Schwartz-Jampel syndrome: a common autosomal recessive syndrome in the United Arab Emirates. Issue 3 (March 1996) - Al-Gazali, L I; Varghese, M; Varady, E; Al Talabani, J; Scorer, J; Bakalinova, D
Abstract : Schwartz-Jampel syndrome (SJS) is a heterogeneous autosomal recessive syndrome of myotonia and bone dysplasia. Two types have been recognised: the classical type with late infantile or childhood manifestation and a rarer form with neonatal manifestation. We report five families with a total of 11 children affected with severe neonatal SJS. All presented after birth with skeletal abnormalities and feeding difficulties. Five had the typical pursed appearance of the mouth. Nine died from respiratory complications (five in the neonatal period and four before 2 years of age). One (4 months old) remains hospitalised since birth requiring continuous oxygen supplementation and one (5 months old) requires nasogastric tube feeding and has repeated attacks of aspiration. Only seven of the 17 previously reported neonatal SJS cases had a similar course to the patients in this report. We suggest that within neonatal SJS there is a subgroup which manifests severe respiratory and feeding problems and has a poor prognosis. This report brings the total number of children with neonatal SJS reported from the UAE to 14. This represents the largest review of this syndrome to date from one centre and indicates that this syndrome is fairly common in the population of the UAE.